Adolescent Pregnancy Complication and Wastage in Bangladesh - Rahman, MM; Hasan, M; Akhtar, S; Sultana, P (Journal of Nepal Paediatric Society, 2010)
Introduction: Pregnancy among adolescents is a health risk for the individual as well as the fetus. The main aim of this study is to examine the pregnancy complications and its outcome among adolescent women in Northern region (Rajshahi) of Bangladesh. Methods: The analysis is based on a part of faculty research; University of Rajshahi funded study on adolescent motherhood and pregnancy complications in the region, which involved a micro level survey of 400 adolescent conception aged 10-19 and in-depth interviews with 37 adolescents who had experienced pregnancy wastage. The indicator of poor pregnancy outcomes analysed includes pregnancy or delivery complications and pregnancy wastage. Results: A striking finding is the higher proportions suffer pregnancy problems, especially in cases of early conception. In particular, younger adolescent aged under 20 years has been observed to have the highest proportions of delivery complications and pregnancy wastage due to insufficient intake foods and possible biological immaturity. Conclusion: Early teenage pregnancy and its effects pose very severe different pregnancy and delivery complications consequently wastage. Key words: Adolescent; Pregnancy; Wastage; Odds ratio DOI: 10.3126/jnps.v30i3.3917 J Nep Paedtr Soc 2010;30(3):147-153